Alveolar macrophages from subjects with chronic obstructive pulmonary disease are deficient in their ability to phagocytose apoptotic airway epithelial cells - Hodge, Sandra; Hodge, Greg; Scicchitano, Raffaele; Reynolds, Paul N; Holmes, Mark (Immunology and cell biology, 2003)
Chronic obstructive pulmonary disease is a highly prevalent, complex disease, usually caused by cigarette smoke. It causes serious morbidity and mortality and costs the global community billions of dollars per year. While chronic inflammation, extracellular matrix destruction and increased airway epithelial cell apoptosis are reported in chronic obstructive pulmonary disease, the understanding of the basic pathogenesis of the disease is limited and there are no effective treatments. We hypothesized that the accumulation of apoptotic airway epithelial cells chronic obstructive pulmonary disease in could be due to defective phagocytic clearance by alveolar macrophages. There have been no previous studies of the phagocytic capacity of alveolar macrophages in chronic obstructive pulmonary disease using physiologically relevant apoptotic airway epithelial cells as phagocytic targets. We developed a phagocytosis assay whereby cultured 16HBE airway epithelial cells were induced to apoptosis with ultraviolet radiation and stained with mitotracker green. Alveolar macrophages from bronchoalveolar lavage from eight control and six chronic obstructive pulmonary disease subjects were analysed following 1.5 h incubation with apoptotic airway epithelial cells, then staining with macrophage marker anti CD33. CD33+/mitotracker green + events (i.e., alveolar macrophages which had phagocytosed apoptotic airway epithelial cells) were analysed using flow cytometry. Phagocytosis of polystyrene microbeads was investigated in parallel. A significantly reduced proportion of alveolar macrophages from chronic obstructive pulmonary disease subjects ingested apoptotic airway epithelial cells compared with controls (11.6 ± 4.1% for chronic obstructive pulmonary disease versus 25.6 ± 9.2% for control group). Importantly, the deficiency was not observed using polystyrene beads, suggesting that the failure to resolve epithelial damage in chronic obstructive pulmonary disease may result, at least partially, from specific defects in phagocytic ability of alveolar macrophages to ingest apoptotic airway epithelial cells.